EFL STUDENTS’ PERCEPTIONS TOWARD CHATGPT AS A WRITING INSTRUMENT - Algrin, Algrin Hayadi; Sofyan, Dedi; Syafryadin, Syafryadin (STKIP Siliwangi, 2025)
The use of AI tools in education is increasing in this age of technological progress. It is essential to comprehend how AI may facilitate the learning process and Assist students in overcoming challenges, particularly in writing.This study examined EFL students' perceptions of ChatGPT as an AI writing instrument. The study employed a qualitative methodology utilizing a phenomenological framework. The data was collected through interviews with five English Education students at the University of Muhammadiyah Bengkulu, selected for their perceived expertise to get comprehensive insights. The collected data was analyzed using theme analysis. The results indicated that students possessed favorable perceptions. Besides, students highlighted ChatGPT's significant role in enhancing the writing process by providing prompt feedback, facilitating idea development, and improving grammatical accuracy. They also found it useful for time management, expanding vocabulary, and generating topics. However, challenges such as ChatGPT's occasional provision of inaccurate information, the risk of fostering dependency, and network-related issues were also noted. Based on these findings, ChatGPT should be used only as a reference or consultation tool; students should use their critical thinking skills and verify ChatGPT responses with reputable sources.This study shows that ChatGPT can help writers, but educators and students must realize its limits.